INTEGRASI SIKAP PEDULI LINGKUNGAN PADA PEMBELAJARAN IPAS MATERI PENCEMARAN LINGKUNGAN KELAS III SDN KERONCONG MAS PERMAI JATIUWUNG KOTA TANGERANG - Zulfa Azzahra, Risyda; Dwi Hartantri, Saktian; Oktrifianty, Erdhita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of integrating an environmentally conscious attitude into IPAS instruction on the topic of environmental pollution for third-grade students at SDN Keroncong Mas Permai and to identify the factors that influence the integration of this attitude. An environmentally conscious attitude is one of the important character values that must be instilled starting in elementary school so that students develop awareness and a sense of responsibility toward environmental sustainability. IPAS instruction, particularly in the environmental pollution unit, serves as a relevant vehicle for integrating these values into learning activities. This study employs a qualitative approach using a descriptive research design. The research subjects included third-grade teachers and third-grade students at SDN Keroncong Mas Permai. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and drawing conclusions, while data validity was ensured through triangulation of techniques and sources. The results of the study indicate that the integration of an environmentally conscious attitude into IPAS lessons on environmental pollution has been implemented through learning activities such as providing examples of environmentally conscious behavior, fostering the habit of keeping the classroom clean, using relevant learning media, and conducting discussions and question-and-answer sessions. Factors influencing the integration of an environmentally conscious attitude include the teacher’s role in planning and implementing instruction, the school environment’s support, environmentally conscious school programs, and student characteristics. Thus, integrating an environmentally conscious attitude into IPAS instruction can help shape students’ character by fostering environmental awareness from an early age.